Contributions of Anterior Corneal and Ocular Residual Astigmatism to Autorefraction Astigmatism in a Myopic Adult Sample - Gab-Alla AA (Dove Medical Press, 2020)
Amr A Gab-Alla Ophthalmology Department, Faculty of Medicine, Suez Canal University, Ismailia, EgyptCorrespondence: Amr A Gab-AllaOphthalmology Department, Faculty of Medicine, Suez Canal University, Ring Road, Ismailia, EgyptTel +20 1222836261Email amrophth@hotmail.comAim: To evaluate the contributions of anterior corneal and ocular residual astigmatism to autorefraction astigmatism in adult myopic and myopic astigmatic subjects and how these compensate each other.Subjects and Methods: This retrospective study was completed in private eye centre, Ismailia, Egypt, between September 2017 and November 2019. The study included eyes with myopia (0.5 to 10.0D) or myopic astigmatism (0 to 8.5D). The refractive errors, including autorefraction astigmatism, were measured after using 1% cyclopentolate with autorefractometer (Topcon, Tokyo Optical Co., Ltd., Japan). Corneal topography (Sirius; CSO, Florence, Italy) was used to measure anterior corneal astigmatism. Ocular residual astigmatism was measured by vectorial subtraction of the anterior corneal astigmatism from autorefraction astigmatism determined to the corneal plane.Results: This study included 1158 eyes (right 582 and left 576) with myopia or myopic astigmatism of 582 participants (206 males with 406 eyes and 376 females with 752 eyes). The mean±SD age of the total participants was 26± 5.7 years, range (21 to 50 years). The mean±SD of spherical error was − 3.2± 1.9D, range (− 0.5 to − 10.0D). The mean±SD of autorefraction astigmatism was 1.13± 1.1D; range (0.5 to 8.5D). The mean±SD of anterior corneal astigmatism was 1.22± 0.8D; range (0.03 to 5.6D). The mean±SD of ocular residual astigmatism was 0.6± 0.5D; range (0 to 4.8D). Of the total eyes, 75.4% had significant autorefraction astigmatism, 82.5% had significant anterior corneal astigmatism, and 16.8% had significant ocular residual astigmatism.Conclusion: The percentage of the significant autorefraction astigmatism (> 0.5D) was 75.4% which is mainly anterior corneal. In 26.8% of participants, anterior corneal astigmatism is compensated by ocular residual astigmatism.Keywords: astigmatism, anterior corneal astigmatism, ocular residual astigmatism, refractive surgeries